A hypothesis and a case-study projection of an influence of MJO modulation on boreal-summer tropical cyclogenesis in a warmer climate with a global non-hydrostatic model: a transition toward the central Pacific? - OOUCHI, KAZUYOSHI; Satoh, Masaki; Yamada, Yohei; Tomita, Hirofumi; Sugi, Masato (Frontiers in Earth Science, 2014)
The eastward shift of the enhanced activity of tropical cyclone to the central Pacific is a robust projection result for a future warmer climate, and is shared by most of the state-of-the-art climate models. The shift has been argued to originate from the underlying El-Ñino like sea-surface temperature (SST) forcing. This study explores the possibility that the change of the activity of the Madden-Julian Oscillation (MJO) can be an additional, if not alternative, contributor to the shift, using the dataset of Yamada et al. (2010) from a global non-hydrostatic 14-km grid mesh time-slice experiment for a boreal-summer case. Within the case-study framework, we develop the hypothesis that an eastward shift of the high-activity area of the MJO, as manifested itself as the significant intra-seasonal modulation of the enhanced precipitation, is associated with the increased tropical cyclogenesis potential over the North central Pacific by regulating cyclonic relative vorticity and vertical shear. In contrast, the North Indian Ocean and maritime continent undergo relatively diminished genesis potential. An implication is that uncertainty in the future tropical cyclogenesis in some part of the Pacific and other ocean basins could be reduced if projection of the MJO and its connection with the underlying SST environment can be better understood and constrained by the improvement of climate models.